Adaptive Responses of Common and Hybrid Bermudagrasses to Shade Stress Associated With Changes in Morphology, Photosynthesis, and Secondary Metabolites - Cao, Yiqin; Yang, Kang; Liu, Wei; Feng, Guangyan; Peng, Yan; Li, Zhou (Frontiers in Plant Science, 2022)
Alteration of ploidy in one particular plant species often influences their environmental adaptation. Warm-season bermudagrass is widely used as forage, turfgrass, and ground-cover plant for ecological remediation, but exhibits low shade tolerance. Adaptive responses to shade stress between triploid hybrid bermudagrass cultivars (‘Tifdwarf’ (TD), ‘Tifsport’ (TS), and ‘Tifway’ (TW)) and tetraploid common bermudagrass cultivar ‘Chuanxi’ (CX) were studied based on changes in phenotype, photosynthesis, and secondary metabolites in leaves and stems. Shade stress (250 luminance, 30 days) significantly decreased stem diameter and stem internode length, but did not affect leaf width of four cultivars. Leaf length of CX, TD, or TW stayed no change in response to shade stress, whereas shade stress significantly elongated the leaf length of TS. The CX and the TS exhibited significantly higher total chlorophyll (Chl), Chl a, carotenoid contents, photosynthetic parameters (PSII photochemical efficiency (Fv/Fm), transpiration rate, and stomatal conductance) in leaves than the TW and the TD under shade stress. The CX also showed significantly higher performance index on absorption basis (PIABS) in leaf and net photosynthetic rate (Pn) in leaf and stem than other three cultivars under shade stress. In addition, the TS maintained higher proantho cyanidims content than the TW and the TD after 30 days of shade stress. Current results showed that tetraploid CX exhibited significantly higher shade tolerance than triploid TD, TS, and TW mainly through maintaining higher effective photosynthetic leaf area, photosynthetic performance of PSI and PSII (Pn and Fv/Fm), and photosynthetic pigments as well as lower Chl a/b ratio for absorption, transformation, and efficient use of light energy under shade stress. For differential responses to shade stress among three triploid cultivars, an increase in leaf length and maintenance of higher Fv/Fm, gas exchange, water use efficiency, carotenoid and proanthocyanidin contents in leaves could be better morphological and physiological adaptations of TS to shade than other hybrid cultivars (TD and TW).